2015
DOI: 10.1016/j.chemphyslip.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Lateral organization, bilayer asymmetry, and inter-leaflet coupling of biological membranes

Abstract: Understanding of cell membrane organization has evolved significantly from the classic fluid mosaic model. It is now recognized that biological membranes are highly organized structures, with differences in lipid compositions between inner and outer leaflets and in lateral structures within the bilayer plane, known as lipid rafts. These organizing principles are important for protein localization and function as well as cellular signaling. However, the mechanisms and biophysical basis of lipid raft formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 202 publications
(214 reference statements)
1
116
0
Order By: Relevance
“…Contributing factors to domain registration could be transmembrane proteins, lipid interdigitation, membrane curvature, line tension, cholesterol flip-flop, and electrostatic interactions (Nickels et al, 2015) of which chain interdigitation has been invoked as the major contributing factor (May, 2009) but also has been totally dismissed (Collins, 2008). A recent experimental determination of the strength of the coupling parameter that causes domain registration matches a theoretical predictions with values around 0.01 k B T /nm 2 (Putzel et al, 2011; Blosser et al, 2015), but considerably higher values have also been suggested from theoretical considerations (May, 2009).…”
Section: The Registration Of Membrane Nanodomains In the Two Leafletsmentioning
confidence: 99%
“…Contributing factors to domain registration could be transmembrane proteins, lipid interdigitation, membrane curvature, line tension, cholesterol flip-flop, and electrostatic interactions (Nickels et al, 2015) of which chain interdigitation has been invoked as the major contributing factor (May, 2009) but also has been totally dismissed (Collins, 2008). A recent experimental determination of the strength of the coupling parameter that causes domain registration matches a theoretical predictions with values around 0.01 k B T /nm 2 (Putzel et al, 2011; Blosser et al, 2015), but considerably higher values have also been suggested from theoretical considerations (May, 2009).…”
Section: The Registration Of Membrane Nanodomains In the Two Leafletsmentioning
confidence: 99%
“…The first widely accepted membrane model (2), the so-called “fluid mosaic model”, assumes that phospholipids are merely structural molecules in which membrane proteins can move freely. This passive description of the membrane lipids is increasingly challenged by recent findings (3, 4, 5, 6). Studies have shown that the membrane is a highly dynamical structure that actively supports the cell function.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that the membrane is a highly dynamical structure that actively supports the cell function. Phospholipids play an important role in this new understanding, for example in conferring membrane curvature (7) and actively organizing proteins complexes (6, 8). Despite these advances, our molecular-level understanding of plasma membranes is still limited, partly due to a lack of experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Through these techniques, a vivid picture of the membrane has emerged. [1419] Nonetheless, they have significant limitations, and fundamental questions about the ultrastructure of the membrane in vivo remain unresolved. [20]…”
Section: Introductionmentioning
confidence: 99%